2004
DOI: 10.1111/j.0953-816x.2004.03126.x
|View full text |Cite
|
Sign up to set email alerts
|

Distributed neuronal networks for encoding category‐specific semantic information: the mismatch negativity to action words

Abstract: Mismatch negativity (MMN), an index of experience-dependent memory traces, was used to investigate the processing of action-related words in the human brain. Responses to auditorily presented movement-related English words were recorded in a non-attend odd-ball protocol using a high-density electroencephalographic (EEG) set-up. MMN was calculated using responses to the same words presented as standard and deviant stimuli in different sessions to avoid contamination from phonetic-acoustic differences. The topog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

19
116
2
2

Year Published

2005
2005
2018
2018

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 177 publications
(139 citation statements)
references
References 60 publications
19
116
2
2
Order By: Relevance
“…On the other hand, this conclusion seems to contradict findings from the ERP literature, specifically the MMN component elicited "pre-attentively" (i.e., without directed attention) in response to a phonemic change in an otherwise repetitive auditory stream (Endrass et al, 2004;Naatanen, 2001;Pettigrew et al, 2004;Pulvermuller & Shtyrov, 2006;Shtyrov et al, 2004). However, it is also known that the MMN can be susceptible to attentional manipulations, as its amplitude is attenuated when participants are engaged in a demanding primary task (e.g., Sabri et al, 2006;.…”
Section: Processing Of Speech Compared To Unfamiliar Rotated Speech Smentioning
confidence: 84%
See 1 more Smart Citation
“…On the other hand, this conclusion seems to contradict findings from the ERP literature, specifically the MMN component elicited "pre-attentively" (i.e., without directed attention) in response to a phonemic change in an otherwise repetitive auditory stream (Endrass et al, 2004;Naatanen, 2001;Pettigrew et al, 2004;Pulvermuller & Shtyrov, 2006;Shtyrov et al, 2004). However, it is also known that the MMN can be susceptible to attentional manipulations, as its amplitude is attenuated when participants are engaged in a demanding primary task (e.g., Sabri et al, 2006;.…”
Section: Processing Of Speech Compared To Unfamiliar Rotated Speech Smentioning
confidence: 84%
“…In a positron emission tomography (PET) study, Price and colleagues found activations associated with task-irrelevant visual word processing in the left posterior temporal lobe, the left inferior parietal lobe, the cuneus, and the left inferior frontal gyrus (IFG) when subjects were engaged in a nonlinguistic visual feature detection task (i.e., detection of one or more ascenders within word and nonword stimuli) (Price et al, 1996). Finally, event-related potential studies of the mismatch negativity (MMN) component provide evidence for detection of lexical or phonemic changes without directed attention to the auditory stream (Endrass et al, 2004;Naatanen, 2001;Pettigrew et al, 2004;Pulvermuller & Shtyrov, 2006;Pulvermuller et al, 2004;Shtyrov et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, the cortical generators of the MMN to words reflect aspects of the meaning of the words eliciting it (Pulvermüller & Shtyrov, 2006;Pulvermüller, Shtyrov, & Ilmoniemi, 2005;Shtyrov, Hauk, & Pulvermüller, 2004). Neuronal network simulations using realistic neuroanatomical architectures underpin these statements and document the non-linear activation-enhancing effect of strongly interconnected distributed memory circuits for words in the human brain (Garagnani, Wennekers, & Pulvermüller, 2008;).…”
Section: A Neurophysiological Perspective On Linguistic Linkagementioning
confidence: 94%
“…With a particular focus on action cognition, empirical neuroscience has demonstrated that sounds, spoken and written words with action-related meaning produce somatotopic semantic activation of the human motor system (in particular motor and premotor cortex) across multiple experimental contexts (Aziz-Zadeh & Damasio, 2008;Grisoni, Dreyer, & Pulvermü ller, 2016;Grisoni, McCormick-Miller, & Pulvermü ller, 2017;Hauk, Johnsrude, & Pulvermü ller, 2004;Hauk, Shtyrov, & Pulvermü ller, 2008;Kana, Blum, Ladden, & Ver Hoef, 2012;Pulvermü ller, Shtyrov, & Ilmoniemi, 2005;Shtyrov, Butorina, Nikolaeva, & Stroganova, 2014;Shtyrov, Hauk, & Pulvermü ller, 2004;Tettamanti et al, 2005). Neural control of movement includes a cascade of cortical areas (primary motor, premotor and supplementary motor cortex, located in precentral gyrus and adjacent sulci [BA 4 and BA 6]) and subcortical regions (such as the striatum and the putamen) along with the cerebellum, most of which have been seen to be activated by words with action affordances .…”
mentioning
confidence: 99%
“…First, although task conditions may suppress it, motor system activation whilst processing action-related stimuli is manifest even if participants do not actively attend to language input (Grisoni et al, 2016;Moseley, Pulvermü ller, & Shtyrov, 2013;Pulvermü ller, Shtyrov, et al, 2005;Shtyrov et al, 2004Shtyrov et al, , 2014Trumpp, Traub, & Kiefer, 2013;Trumpp, Traub, Pulvermü ller, & Kiefer, 2014). Second, motor activation during processing of action language is flexible, following the pattern expected for semantic mechanisms (for discussion, see .…”
mentioning
confidence: 99%